Provenance discrimination and Source-to-Sink studies from a dryland fluvial regime: An example from Kachchh, western India - Prizomwala, S.P.; Bhatt, Nilesh; Basavaiah, N. (My University, 2014)
Tracing the sediment delivery from its source terrain to its ultimate sink envisage multiple factors that play a vital role in understanding present day erosional engine. To accomplish this, it is significant to distinguish the variable end-members contributing to the basin. The findings from the study of dryland coastal fluvial regime in Kachchh (Western India), which is one of the end members contributing to the Gulf of Kachchh coast (partial sink) and finally to the Arabian Sea (ultimate sink) have been presented here. Multi-proxy sediment provenance proxies such as grain-size, clay minerals, geochemistry and magnetic minerals have been employed to evaluate the provenance discriminating characteristics of the Kachchh dryland fluvial system and factors influencing them. The results of different proxies indicate that the provenance signatures of uplands are quite characteristic with magnetic susceptibility (χ) values of <2010−7 m3 kg−1 and smectite (S)/kaolinite (K) ratio between 0.26 and 0.49. The middle reaches show marked increase in magnetic mineral concentration with χ values (14010−7 m3 kg−1) and S/K ratio (4.92), while the estuarine tract shows χ values (8010−7m3 kg−1), S/K ratio (1.90) and, characteristic heavy minerals (i.e. mica minerals), probably reflect the interplay between land and sea oscillations. Major sources of sediments within catchment scale were identified, viz., upland sedimentary rocks (Juran and Bhuj Formation sandstone-shale) and middle reaches volcanic (Deccan Trap Formation basalt) rocks. The present study draw cautions in provenance of sediment discrimination in areas influenced by Deccan basalt that has the overwhelming sediment delivery and a comparatively subdued effects of other provenance signatures. The studied proxies of mineralogy of clays, magnetic minerals and geochemistry of heavy and major elements serve as the potential for fingerprint of sediment source regions and hence behold a strong position in source to sink studies globally.
Keywords: Provenance; Source-to-sink; Heavy minerals; Clay minerals; Kachchh